SECOND LANGUAGE ACQUISITION THEORIES AND THEIR RELATIONSHIP TO AI TOOLS. (Лучшие интеллектуальные исследования, 2025)
This article studies the interconnection between second language acquisition theories (SLA) and Artificial Intelligence(AI) tools in modern language education. By analyzing key theories SLA - including Krashen’s input hypothesis, Long’s interaction hypothesis, Swain’s output hypothesis, Schmidt’s noticing hypothesis, and Vygotsky’s sociocultural theory, it discusses how AI technologies can be designed to improve the process of language learning. The main focus is on adaptive educational environments,  AI-mediated interactions, feedback mechanisms, and socio-cognitive support tools. As AI becomes more integrated into educational process, there is a growing need for theoretical aspects of education for ensuring ethical, effective, and pedagogically sound tool development.